THE IMPACT OF PRIVACY, SECURITY, AND TRUST ON ONLINE TRANSACTION INTENTIONS AT BANK BCA BANDUNG - Eva Purnamasari; Asri Ady Bakri; Eko Cahyo Mayndarto (Pusat Riset dan Inovasi Nasional, 2023)
Bank BCA is one of the banks that strengthens its efforts in developing service products by utilizing the internet to make online transactions. So this study aims to determine the effect of privacy, security, and trust on the intention to transact online at Bank BCA Bandung. The method used in this research is a quantitative descriptive method. Research location at Bank BCA Bandung No. 18 in October 2022. The population is customers who visited in the October 2022 period. Sampling was carried out using an incidental sampling technique with a total of 97 customers. Data collection techniques using a questionnaire. Data analysis techniques were performed using the t-test and F-test. The results of the study found that privacy, security, trust has a simultaneous and partial effect on the intention to transact online at Bank BCA Bandung. The effect is 51.9%, while the remaining 48.1% is influenced by other variables not examined in this study